World of Labour: Contours of the Future - G. L. Podvoisky (Мир новой экономики)
Serious transformations will take place in the economy of many countries in the XXI century under the influence of a powerful wave of a new technological revolution that is unfolding at the present time. According to scientists and experts, the new technologies will not only seriously change the image of many industries, but also affect the entire economic structure. This process, in turn, will lead to profound changes in the sphere of labour. The author considers various scenarios of labor market development, paying special attention to new professions that may appear and will be in demand, and which professions will be transferred to the category of expiring ones. The emergence of new professions makes new demands on the Russian education system at all levels and requires its modernization so that its reset will allow qualified workers to be trained for all spheres of the economy.